2019
DOI: 10.1107/s160057751900660x
|View full text |Cite
|
Sign up to set email alerts
|

A versatile nanoreactor for complementary in situ X-ray and electron microscopy studies in catalysis and materials science

Abstract: Two in situ `nanoreactors' for high-resolution imaging of catalysts have been designed and applied at the hard X-ray nanoprobe endstation at beamline P06 of the PETRA III synchrotron radiation source. The reactors house samples supported on commercial MEMS chips, and were applied for complementary hard X-ray ptychography (23 nm spatial resolution) and transmission electron microscopy, with additional X-ray fluorescence measurements. The reactors allow pressures of 100 kPa and temperatures of up to 1573 K, offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…In order to expand the experimental capabilities of PtyNAMi towards heterogeneous catalysis research, a series of in situ sample environments were developed for the instrument, described in detail in a previous publication by Fam et al (2019). In summary, the in situ cells [see Fig.…”
Section: In Situ Hard X-ray Ptychographymentioning
confidence: 99%
See 2 more Smart Citations
“…In order to expand the experimental capabilities of PtyNAMi towards heterogeneous catalysis research, a series of in situ sample environments were developed for the instrument, described in detail in a previous publication by Fam et al (2019). In summary, the in situ cells [see Fig.…”
Section: In Situ Hard X-ray Ptychographymentioning
confidence: 99%
“…The setup is optimized in order to enable scanning hard X-ray microscopy with the highest possible spatial resolution and sensitivity using the aforementioned X-ray analytical contrast mechanisms, and it provides all degrees of freedom required for 2D and 3D imaging experiments (Kahnt et al, 2019). It is furthermore compatible with additional auxiliary experimental equipment required for in situ or operando experiments (Fam et al, 2019). The instrumental design was developed following the experimental requirements for highresolution X-ray ptychography, which may be summarized as (i) high-performance X-ray optics (Section 4), (ii) high mechanical stability and control (Section 5), (iii) low scattering background (Section 6), (iv) optimized coherent flux (aperture matching).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 67 69 Furthermore, they recently reported on the fabrication of two nanoreactors for in situ electron and X-ray tomographic studies, allowing pressures and temperatures of up to 100 kPa and 1573 K with a tilting angle of ±35° for a fully mounted cell. 70 The van Bokhoven group recently reported on a 3-D estimated spatial resolution between 30 and 40 nm for the subvolume of several fluid catalytic cracking (FCC) catalyst particles using ptychographic X-ray-computed tomography (PXCT). 71 74 They found that zeolite amorphization and structural changes are the underlying driving forces for the FCC catalyst deactivation process.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to conventional X-ray full-field microscopy, X-ray ptychography offers superior resolution, reaching into the single-digit nanometer range 15,16 . X-ray ptychography is well suited for in situ and operando measurements and has been utilized to study various physical and chemical processes [17][18][19][20] . In all cases, the sample is enclosed inside some sample environment that is penetrated by the X-rays during the measurement.…”
mentioning
confidence: 99%